Investigation of the relationship between alexithymia and eating attitude, self-esteem and anger in women who applied to psychological counseling center - Ünübol, Hüseyin; Hızlı Sayar, Feride Gökben; Kanbolat, Sinem (The European Research Journal, 2018)
Objective: The main purpose of this study was to examine self-esteem, anger and eating attitude with alexithymia in people who consult to the psychological counseling center. The sample of the study consist of 100 women who were located in Istanbul and applied to the psychological consulting center.Methods: Consent form, demographic form, State-Trait Anger Expression Inventory, Rosenberg Self-Esteem Inventory, Toronto Alexithymia Scale and Eating Attitude Test have been used to collect the data in this study. In this research, the relationship between sociodemographic features, alexithymia, self-esteem, anger, eating attitude of women who consult to the psychological counseling center had been examined. Data obtained have been analyzed statistically by using SPSS 15.0 for Windows.Results: The findings of this research supported our hypothesizes. Regarding the relationship between eating attitude and alexithymia, there is a positive relationship between difficulties in identifying and describing feelings with eating attitudes (p < 0.05). Regarding the relationship between alexithymia and self-esteem, there is a positive relation between sub-dimensions of alexithymia scale with subscales of self-esteem (p < 0.05). There is a positive relationship between identifying feelings with trait anger and anger-out scores (p < 0.05).Conclusions: According to these results, it appears that alexithymia has a serious relationship with anger, eating attitude and self-esteem. We suggest that alexithymia may be at the center of other features relations with each other.